2020
DOI: 10.3390/polym12122814
|View full text |Cite
|
Sign up to set email alerts
|

Impact Strengthening of Laminated Kevlar/Epoxy Composites by Nanoparticle Reinforcement

Abstract: Herein, we report the fabrication and characterization of high-strength Kevlar epoxy composite sheets for structural application. This process includes optimization of the curing conditions of composite preparation, such as curing time and temperature, and the incorporation of nanofillers, such as aluminum oxide (Al2O3), silicon carbide (SiC), and multi-walled carbon nanotubes (MWCNT) in different weight percentages. Differential scanning calorimetry (DSC) was utilized to investigate the thermal stability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 47 publications
0
9
2
Order By: Relevance
“…Additionally, Merah et al [ 28 ] reported brittle fracture and a reduction in ultimate strain after prolonged exposure to seawater. In general, the prolonged seawater immersion causes plasticization and swelling in the composite material and affects the tolerance capacity of the composite material [ 29 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Merah et al [ 28 ] reported brittle fracture and a reduction in ultimate strain after prolonged exposure to seawater. In general, the prolonged seawater immersion causes plasticization and swelling in the composite material and affects the tolerance capacity of the composite material [ 29 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Flexural test results reflect the combined effects of tensile, compressive, and shear properties. The flexural modulus (E f ) represents resistance to bending deformation [39]. Thus, flexural properties are important for the ballistic application.…”
Section: Flexural Behaviormentioning
confidence: 99%
“…For material effectiveness, it is essential to ensure the durability of FRP composites in the seawater environment. Nanofillers are one effective solution for closing any gaps and increasing the compositional intensity [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Several studies have been performed in different aging conditions for the performance of epoxy-based composites.…”
Section: Introductionmentioning
confidence: 99%